Pengaruh Brand Awareness, Tingkat Kepercayaan, Transparansi, Akuntabilitas Dan Tingkat Pendapatan Generasi Milenial Terhadap Pembayaran Zakat Melalui Lembaga Baznas Secara Online: (Studi Pada Generasi Milenial Sumatera Utara) - Obit Dwi Pratama; Mustafa Kamal Rokan; Nurul Inayah (Pusat Riset dan Inovasi Nasional, 2024)
The millennial generation is very techno minded, where they interact using gadgets in their daily activities, so they have the potential to become muzakki, especially in online zakat payments. There are several perceptions of the millennial generation in paying zakat online, namely awareness, level of trust, transparency, accountability and income level. The aim of this research is to determine the influence of brand awareness, level of trust, transparency, accountability and level of income on online payments and to determine the most dominant independent variables in online zakat payments. The type of data collected was primary data by distributing questionnaires directly to the millennial generation, totaling 100 respondents. The analysis method used is multiple linear regression analysis and assisted with SPSS 20. The research results show that brand awareness and the level of trust have a positive and significant influence on online zakat payments. Transparency, accountability and income level do not have a positive and insignificant influence on online zakat payments. The most dominant variable influencing online zakat payments is the level of trust.